Statistical and Economic Analysis Of Zonal Conditions Impact On Efficiency Of Cattle Production Supply Chain Management - Aigul Hazieva; Nuria Rafikova; Gamir Khabirov; Alisa Ableeva; Guzel Salimova; Zaria Zalilova; Elena Kabashova; Nuria Valishina (International Journal of Supply Chain Management, 2019)
The article presents the results of an economic and statistical analysis of the effect of zonal conditions on the supply chain (supply chain) of products, production and cost of products for growing and fattening cattle separately from dairy and meat cows. Typological groupings of agricultural organizations of the Republic of Bashkortostan based on average annual data for 2014-2016 were used as a toolkit of analysis, which made it possible to obtain more reliable estimates compared with the grouping for a particular year. Significant differences in the supply chain between zones, as well as between areas in the context of individual zones were found, there were also identified three groups of areas in terms of costs, productivity and cost of production. There were revealed features of the cost structure, productivity level and wages in cattle breeding in the context of zones. Multiple correlation-regression models of livestock productivity and production costs for all areas and zones were built, which made it possible to determine the most significant factors. The obtained results should be used in the development of strategies and planning for organizing the management of the supply chain of products, as well as the location, production specialization, taking into account the influence of natural and climatic conditions and the availability of natural forage lands to ensure efficient production of cattle breeding.